JOB SATISFACTION OF EMPLOYEES IN SELECT SUGAR MILLS IN TAMIL NADU - V.SATHIYA (International Journal of Psychosocial Rehabilitation, 2020)
Job satisfaction must be an integral part of our life and organization strategy. Need are increasing day by day.Today every person is engaged in a job like customer services, stocking, and flow of goods. Since increase in productivity is the ultimate goal of every industrial organization, job satisfaction of employees at all levels is the most critical function of management. Employees who have higher job satisfaction are usually less absent, less likely to leave, more productive, more likely to display organizational commitment, and more likely to be satisfied with their lives. To the workers, job satisfaction brings a pleasurable emotional state that often leads to a positive job attitude. A satisfied worker is more likely to be creative, flexible, innovative, and loyal.The worker and employer both are concerned with it. The employer is interested because it results in good production. The worker is concerned with it because it brings happiness to him. Therefore, job satisfaction of employees in any organization is of paramount importance to achieve the targeted goals on a sustainable basis. In this context, the researcher has made an attempt to study the job satisfaction of employees in the select sugar mills in Tamil Nadu.